Effect of vibrationally excited N2(v) on atomic nitrogen generation using two consecutive pulse corona discharges under atmospheric pressure N2. (19th September 2019) - Teramoto, Yoshiyuki; Kim, Hyun-Ha
Abstract: Herein, we report on experimental results showing that vibrationally excited N2 ( v ) plays an important role in producing nitrogen atoms in successive two-pulsed corona discharges. To investigate the effect of vibrationally excited N2 ( v ) on the generation of atomic nitrogen, two pulses were generated such that their pulse intervals could be varied in a controlled manner. The resulting nitrogen atoms were measured using TALIF under atmospheric pressure N2 at different time points after each pulse. Firstly, the effect of pulse-to-pulse intervals (Δ t ) on the streamer formation of the second pulse discharge was observed. The results suggest that a decrease of Δ t cause a reduction in the consumption of energy and inhibit streamer formation and propagation of a second pulse discharge. The energy efficiency of atomic nitrogen generation in the second pulse discharge near the anode tip was a maximum of approximately three times that of the first pulse. This efficiency decreases with increasing Δ t and eventually became approximately equivalent to the value of the first pulse within Δ t   =  300 µ s. This behavior is correlated with the temporal profile of the vibrational temperature after pulse discharge, which indicates that vibrationally excited N2 ( v ) generated by the first pulse discharge plays a significant role in atomic nitrogen generation in the second pulse. The local densities of atomic nitrogen in the streamer channel for the first and second pulse discharges were estimated from their decay rate. The results suggest that the second pulse discharge generates atomic nitrogen while maintaining the local density of the first discharge pulse in the streamer channel, irrespective of Δ t . Moreover, it indicates that the main generation region of atomic nitrogen in the second pulse discharge is different from that of the first pulse, although the second pulse discharge uses vibrationally excited N2 ( v ) to generate atomic nitrogen.